Diversifying farms in Guinayangan, Philippines - Rio, S. del; Anunciado, M. S; Monville-Oro, Emilita; Gonsalves, Julian Francis; Hunter, D.; Borelli, T; Mendonce, S (2023)
In rural areas where malnutrition is higher and households poorer, growing diverse fruit trees-especially indigenous fruits-can provide multiple benefits. These fruit trees can be a valuable source of secondary income in rural areas such as Guinayangan, where coconut cultivation is the primary source of income. They are also a viable strategy to promote climate-smart agriculture which can strengthen the resilience of farmers; and to diversify agricultural systems for better nutrition within the community.